Evaluation of serum periostin level in atopic dermatitis patients - Afaf H Ghanem; Fathia M Khattab; Amal Zidan (Wolters Kluwer Medknow Publications, 2017)
Background Atopic dermatitis (AD) is a chronic, pruritic inflammatory skin disease. Periostin is an intrinsic mediator induced by T helper-2 cytokines. It has been reported to play a critical role in the pathogenesis of AD. Objective The objective of this study was to estimate the serum periostin level in AD patients and to determine its correlation with the severity and chronicity of the disease. Patients and methods This study included 36 AD patients and 36 healthy controls, matched for age and sex. Three millimeters of venous blood was collected from each patient. Serum periostin level was determined by enzyme-linked immunosorbent assay. We determined the correlation between serum periostin level, duration of disease, severity, type of atopy, and SCORAD score. Results There were highly significant differences between patients and controls as regards serum periostin level (P<0.001). There were significant differences between severe AD patients in serum periostin level, with an increased level among those with severe degree (P<0.001). There were significant differences in serum periostin level among the widespread type (P=0.03). Furthermore, there were significant positive correlations between periostin level and both duration and SCORAD score of the patient group. Conclusion Serum periostin level may correlate with disease severity and chronicity in patients with AD.